Manajemen Sistem Administrasi Berbasis Teknologi dalam Meningkatkan Mutu Tenaga Pendidik di Madrasah Tsanawiyah Negeri 2 Bengkulu Selatan - Wardatul Janah; Ermi Aprilia (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: The quality of educators still seems difficult to realize, because the management of the technology-based administrative system has not been optimally carried out, this can be seen that there are still educators who are not able to fill in the value of technology-based report cards. The purpose of the research is to describe and analyze the management of technology-based administrative systems in improving the quality of educators in Madrasah Tsanawiyah Negeri 2 Bengkulu Selatan. Using a descriptive qualitative method. The results of the study show that the management of the technology-based administrative system in general has been managed well, but there are still educators who have not been able to manage properly, especially in the management of report card assessments, so that there are often assessment errors, educators in general have been of good quality, but there are still educators who are not of good quality, this can be seen at the level of learning management ability such as learning program planning, The organization of learning, the implementation of learning and the supervision or evaluation of learning outcomes have not been optimally implemented. So it can be concluded that technology-based administrative system management can improve the quality of educators, so it can be suggested, if you want to improve the quality of educators, then improve the management of technology-based administrative systems in Madrasah Tsanawiyah Negeri 2 Bengkulu SelatanKeywords: Management, Technology-Based Administration System, Quality of Educators. Abstak: Mutu tenaga pendidik masih terkesan sulit diwujudkan, karena manajemen system administrasi berbasis teknologi belum optimal dilakukan, hal ini terlihat masih ada tenaga pendidik belum mampu mengisi nilai rapot berbasis teknologi. Tujuan penelitian untuk mendeskripsikan dan menganalisis manajemen system administrasi berbasis teknologi dalam meningkatkan mutu tenaga pendidik di Madrasah Tsanawiyah Negeri 2 Bengkulu Selatan. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa manajemen system administrasi berbasis teknologi secara umum telah dikelola dengan baik, namun masih ada tenaga pendidik belum mampu mengelola secara baik, khususnya dalam pengelolaan penilaian raport, sehingga sering terjadi kesalahan penilaian, tenaga pendidik secara umum telah bermutu, namun masih ada tenaga pendidik yang belum bermutu, hal ini terlihat tingkat kemampuan manajemen pembelajaran seperti perencanaan program pembelajaran, pengorganisasi pembelajaran, pelaksanaan pembelajaran dan pengawasan atau evaluasi hasil pembelajaran belum optimal dilaksasanakan. Sehingga dapat disimpulkan bahwa manajemen system administrasi berbasis teknologi dapat meningkatkan mutu tenaga pendidik, sehingga dapat disarankan, jika ingin meningkatkan mutu tenaga pendidik, maka tingkatkan manajemen system administrasi berbasis teknologi di Madrasah Tsanawiyah Negeri 2 Bengkulu SelatanKata kunci: Manajemen, Sistem Administrasi Berbasis Teknologi, Mutu Tenaga Pendidik.